2005
DOI: 10.1038/sj.ijo.0803116
|View full text |Cite
|
Sign up to set email alerts
|

Resistin concentrations before and after weight loss in obese children

Abstract: Objective: The influences of gender, puberty, and obesity on resistin levels and the longitudinal relationships between insulin resistance, weight loss, and resistin have not yet been studied in childhood. Methods: Age, pubertal stage, gender, weight status (standard deviation score-body mass index (SDS-BMI)), resistin levels, and insulin resistance index calculated by homeostasis model assessment (HOMA) were evaluated in 63 obese children and compared to 36 lean children of same age, gender, and pubertal stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
1
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
6
20
1
6
Order By: Relevance
“…Indeed, it has been shown that human resistin is mainly expressed by macrophages and not by adipocytes. 1 Some cross-sectional human studies failed to show differences in resistin expression between lean and obese subjects 6,7,31 while others observed a direct association between resistin and markers of adiposity. 3,10,32 Also, human intervention studies produced inconsistent results with respect to changes in body weight or other measures of adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that human resistin is mainly expressed by macrophages and not by adipocytes. 1 Some cross-sectional human studies failed to show differences in resistin expression between lean and obese subjects 6,7,31 while others observed a direct association between resistin and markers of adiposity. 3,10,32 Also, human intervention studies produced inconsistent results with respect to changes in body weight or other measures of adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…En sujetos de edad pediátrica, se ha reportado diferencia significativa entre eutróficos y obesos [11][12][13][19][20][21][22] y se ha encontrado correlación positiva entre resistina e IMC 9,19,21 , relación que es considerada por algunos autores como fuerte e independiente de la edad, género y estadio puberal, en obesos 22 . Por el contrario, se ha reportado que no existe diferencia significativa en los niveles de resistina entre eutróficos y obesos 1,3,5,9,23,[24][25][26] o correlación entre ambas variables 1,23,25,27 .…”
Section: Discussionunclassified
“…Los resultados de esta investigación, muestran diferencia significativa entre géneros en el grupo de eutróficos, presentando el femenino el nivel de resistina más elevado. Igualmente algunos trabajos reportan diferencias entre géneros con niveles de resistina mayores en el femenino, sin importar el estado nutricional 9,11,20,25 , en eutróficos y obesos por separado 9 y en los púberes 11 . Sin embargo, otros autores no han podido establecer diferencia entre géneros 1,5,13,21,22 .…”
Section: Discussionunclassified
See 2 more Smart Citations